Evolution of the Literary Hero The Relationship in the Concepts of Wrestlers and Heroism in the Uzbek Prose - Mahbuba Ismonaliyeva Jabarali qizi (Zien Journals, 2023)
The article depicts the formation of the concept of a literary hero in relation to the national heroes of Western and Eastern nations. The semantic closeness of the lexemes "hero" and "pahlavan"(wrestler) and the fact that the word "pahlavan" took the form of "powlon" are highlighted. The renewal of artistic thinking in Turkish literature by the 20th century, the activation of the image of a wrestler in Uzbek prose in the 70s, and the influence of heroic features in its creation are analyzed
Keywords: the concept of a hero; gods and heroes of antiquity; heroic features; Eastern mythology